A critical review of phase change material composite performance through Figure-of-Merit analysis: Graphene vs Boron Nitride - Usman Bin Shahid (14152089) (2021)
Phase change materials (PCMs) as a medium for thermal energy storage may hold the key to solving the intermittent energy supply of renewable sources like solar and wind energy. However, the low thermal conductivity of PCMs is currently a significant bottleneck to effectively extract and release energy as required. A considerable research effort is being made to address the low thermal conductivity of PCMs using thermally conductive nanofillers. This review provides a critical analysis of current progress in this field, focusing primarily on graphene-based fillers and boron nitride nanofillers. We also employ here, for the first time, a figure-of-merit (FOM) approach to critically assess the impact of the filler type and loading, the processing method, and the PCM matrix on the performance of these PCM composites. We also propose a standard protocol to improve the data reporting practice in this field, such that a uniform platform for assessing these PCM composites' performance can be established. Other Information Published in: Energy Storage Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ensm.2020.10.004